The Carolingian world - Costambeys, Marios; Innes, Matthew; MacLean, Simon (Cambridge ; New York : Cambridge University Press, 2011)
"At its height, the Carolingian empire spanned a million square kilometres of Western Europe--from the English Channel to central Italy and northern Spain, and from the Atlantic to the fringes of modern Hungary, Poland, and the Czech Republic. As the largest political unit for centuries, the empire dominated the region and left an enduring legacy for European culture. This long-awaited and comprehensive survey traces this great empire's history, from its origins around 700, with the rise to dominance of the Carolingian dynasty, through its expansion by ruthless military conquest and political manoeuvring in the eighth century, to the struggle to hold the empire together in the ninth. It places the complex political narrative in context, giving equal consideration to vital themes such as beliefs, peasant society, aristocratic culture, and the economy. Accessibly written yet authoritative, this book offers distinctive perspectives on a formative period in European history"--
The creation of Carolingian kingship to 800 -- Belief and culture -- Inventing the Carolingian empire : politics and government, 800-840 -- Villages and villagers, land and landowners -- Elite society -- Exchange and trade : the Carolingian economy -- Sustaining the Carolingian empire : politics and government, 840-888 -- Epilogue.
Includes bibliographical references and index.
Keywords: Carolingians -- History; Civilization, Medieval; France -- History -- To 987.; France -- Civilization; Europe, Western -- History; Europe, Western -- Civilization; Europe -- History -- 476-1492.